Function and Sacrality of Philoctetes' Bow - Pérez Lambás, Fernando (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2019)
The bow of Philoctetes, as a symbolic and sacred object, has been studied many times. However, its importance as a sacred weapon deserves a revision regarding the religious and epic contexts of the author. According to the general view, this sacred quality comes from the divine provenience of the bow, which belonged to Heracles. Nevertheless, in some passages it could be best explained by the sacred significance that some objects had in certain religious contexts.